COMPARATIVE STUDY BETWEEN EARLY AND LATE LAPAROSCOPIC CHOLECYSTECTOMY IN TREATMENT OF ACUTE CHOLECYSTITIS IN BUNDELKHAND REGION - RAMESH CHANDRA ARUN; MANOJ KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Laparoscopic cholecystectomy is considered the procedure of choice for patients presenting with acute cholecystitis. The following study is an attempt to compare the outcome and operative complications of early versus late laparoscopic cholecystectomy in patients presenting with acute cholecystitis in a tertiary care center in Banda district of bundelkhand region. Methods: The present study involved a review of case records of 80 patients with the clinical diagnosis of acute cholecystitis, admitted in the surgical wards of a tertiary care center of Banda district during the period from January 2023 to December 2023 who underwent laparoscopic cholecystectomy on an elective basis. Participants were divided into two groups, Group A (early laparoscopic cholecystectomy) and Group B (delayed laparoscopic cholecystectomy) containing 40 patients each. The hospital records of these patients were reviewed and analyzed. Results: The present study showed statistically significant differences in age distribution and duration of surgery. The average duration of surgery was 42.3±8.97 min in Group “A” and 53.5±9.87 min for Group “B.” Male-to-female ratio was 2:1. The rate of conversion was found to be 2.5% in Group “A” as compared to 10% in Group “B.” Post-operative complications such as wound infection and biliary leakage were more common in Group “B” in comparison of Group “A.” Conclusion: Early cholecystectomy can be considered a safe and better method of treatment for acute cholecystitis due to its shorter hospital stay, avoidance of readmission to hospital, and decreased overall costs of treatment which is a major economic benefit to both the patient and health care system in comparison of late cholecystectomy.